The Effect of Compensation, Training, and Work Discipline on Employee Performance - Nadia Saputri; Mella A Listia; Syifa Fauzatuz Zulfa (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This study aims to test or analyze how employee performance affects compensation, training, and work discipline. Design/methodology/approach – This study uses quantitative research methods, using primary data collected from a population of 70 employees who are members of PT Namicoh Indonesia Component in the automotive manufacturing section of plant 1. Each questionnaire distributed contained 54 statements to be answered by respondents. To get the results of this study, researchers used SEM-PLS (Partial Least Squares) version 3.0. Findings – The results of this study in the first hypothesis found that compensation has a positive and significant effect on employee performance, then the second hypothesis found that training has a positive and insignificant effect on employee performance, then the third hypothesis found that work discipline has a positive and insignificant effect on employee performance Research limitations/implications – This research introduces innovative variables in employee performance. In particular compensation, training, and work discipline, which provide new insights. However, these findings are limited to PT Namicoh Indonesia Component automotive manufacturing plant 1, and broader applicability to non-automotive manufacturing company contexts requires further research.